Health assessment of non-native red-eared sliders (Trachemys scripta elegans) and their impact potential on native species - John M. Winter; Kaitlin Moorhead; Kamila Grochowski-Grum; Chris Anchor; Jennifer A. Landolfi; Laura A. Adamovicz; Matthew C. Allender (PLoS ONE, 2025)
Red-eared sliders (RES; Trachemys scripta elegans) are a globally invasive species that can impact native chelonian populations through resource competition and disease introduction. In Cook County, Illinois, invasive RES co-occur with, and greatly outnumber, a species of conservation priority in the Great Lakes region: the Blanding’s turtle (Emydoidea blandingii). This study sampled free-ranging RES in Cook County during spring, summer, and fall in four unique locations to characterize the possible effect of this non-native species on the health of regional, sympatric, aquatic chelonians. RES (n = 242) were captured and sampled for qPCR pathogen detection, clinical pathology, and necropsy from 2018 to 2022. Multiple pathogens were detected, including Mycoplasma spp., multiple adenoviruses, Trachemys herpesvirus 1 (TrHV-1), frog virus 3, human-pathogenic Leptospira spp., Emydomyces testavorans, and Salmonella typhimurium. Mycoplasma spp. prevalence was significantly higher (p < 0.05) at one isolated site with a suspected greater density of turtles. Detection of TrHV-1 was significantly associated with season (p < 0.001), with detections occurring only in spring and fall. For the 28 hematology, plasma biochemistry, and protein electrophoresis analytes assayed, significant and variable associations occurred based on sample year, season, pathogen detection, age, and sex. Population-based reference intervals were created for hematologic, plasma biochemistry, and plasma protein electrophoresis analytes. Common necropsy findings included mild endoparasitism and related vascular lesions such as endarteritis. Notably, qPCR detection of above pathogens was not associated with any gross or histologic lesions indicative of clinically relevant disease. This study indicates that invasive RES in Cook County may be infected with pathogens of concern for co-occurring turtle species, and absence of associated lesions in the RES suggests they likely serve as carrier species for these pathogens. Continued health monitoring of this species is important as interactions with chelonians of conservation priority increase.